Pengaruh Artificial Intelligence Berbasis Chat terhadap Efektivitas dan Efisiensi Penyelesaian Masalah Pembelajaran di Tingkat Perguruan Tinggi - Angruningrum, Erinna; Meitridwiastiti, Anak Agung Ayu; Pratama, Muhammad Ahyar; Utami, Luh Putu Rika; Ameria, Dewa Ayu Dinar Kartika; Putra, Kadek Prema Sadhana (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
This study aims to evaluate the effectiveness and efficiency of the use of artificial intelligence (AI) in the scope of higher education and to see how important the role of artificial intelligence (AI) is in solving problems in the university environment. The research will involve surveys and interviews with individuals who have experience in the application of AI in college. This research will also use the Unified Theory of Acceptance and Use of Technology (UTAUT) method as a direction in making a question survey that will be disseminated to respondents. The goal of this study is to provide a better understanding of how quickly and effectively AI can solve problems in a college environment. This study will use qualitative and quantitative approaches, where the results of the research will be explained qualitatively through interviews and quantitatively through statistical analysis of Simple Linear Regression from the results of the respondents.